Unique Adsorption Properties of Cationic Dyes Malachite Green and Rhodamine-B on Longan (Dimocarpus longan) Peel - Risfidian Mohadi; Normah; Erni Salasia Fitri; Neza Rahayu Palapa (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
This research converts agricultural waste Longan (Dimocarpus longan) Peel is used in the adsorption process to reduce cationic dyes rhodamine-B and malachite green contaminants from aqueous solution. Longan (Dimocarpus longan) Peel was characterized by FT-IR, analysis XRD, SEM, BET, and TG-DTA. The characterization results show that Longan (Dimocarpus longan) Peel contains cellulose compounds and has a specific surface area 17.175 m2/g, with this Longan (Dimocarpus longan) Peel has the potential as a bio adsorbent. The adsorption capacity is proven by adsorption capacity (Qm) shows that the bioadsorbent adsorption of malachite green has a large adsorption capacity of 182.64 mg/g, while the adsorption capacity of rhodamine-B (Qm) reaches 52.557 mg/g and this bioadsorbent longan (Dimocarpus longan) peel is effective the adsorption was stable until the third cycle.